PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) ELEKTRONIK DENGAN FLIP PDF PROFESSIONAL BERBASIS PENDEKATAN KONSTRUKTIVISME PADA MATERI SISTEM RESPIRASI KELAS XI SMA - Herma Willia Safitri; Wan Syafi’i; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce an electronic Student Worksheet (e-LKPD) with Flip PDF Professional based on the Constructivism Approach on Respiration System Materials for Class XI SMA. The research was carried out at the Biology Education Study Program, FKIP UNRI and at the zoom meeting platform for SMA Negeri 1 Pekanbaru students from June to September 2021. This type of research used the ADDIE model. The instruments used are validation sheets and response questionnaires. The results of the validation of the electronic LKPD with Flip PDF Professional based on the Constructivism Approach in Class XI High School Respiration System Materials show that the electronic LKPD that has been developed is in the very valid category with an overall average score of 3.86. The results of the first stage of the trial obtained an average score of 3.48 and the results of the second stage of the trial obtained an average score of 3.49 in the very good category. Based on the results of the analysis of students' answers to the electronic LKPD from the constructivism stage, namely idea generation, idea structure, idea application and reflection, an average score of 3.75 was obtained. The results showed that the well-developed electronic worksheets were suitable to be used as a reference for learning in schools as well as independent learning resources to increase students' knowledge and understanding of the respiratory system material in facilitating students to build their own knowledge.Key Words: Electronic Student Worksheet, Constructivism Approach, Respiratory System.